Development of a Goat Manure Shredding Machine as an Appropriate Technology for Organic Fertilizer Production - Yoto Yoto; Didik Nurhadi; Marsono Marsono; Agus Suyetno; Muhammad Idris Effendi; Putrinda Inayatul Maula (Universitas Islam Raden Rahmat, Malang, 2025)
This study aimed to develop and test an appropriate technology in the form of a goat manure shredding machine to enhance organic fertilizer production and improve waste management efficiency. The research adopted a 4-D development model comprising Define, Design, Develop, and Disseminate stages. Initial problem analysis was conducted through field observations and farmer interviews. Based on these findings, a prototype shredding machine was designed and fabricated using a 7 HP gasoline engine with adjustable rotation speeds. The machine was then tested in both workshop and field environments. Fifteen local farmers participated in the field implementation, which included technical training and composting trials. The performance test showed that the machine could process 10 kg of goat manure in 5.23 minutes at low speed and 2.12 minutes at high speed, resulting in a maximum shredding capacity of 283.02 kg/hour. The shredded manure accelerated the composting process, producing mature organic fertilizer within 21–28 days. The final compost exhibited optimal physical characteristics, including dark color, neutral odor, and balanced moisture content. Additionally, farmers reported increased skills, reduced labor burden, and growing interest in commercializing the compost product. In conclusion, the developed shredding machine proved effective in addressing manure waste challenges, enhancing composting efficiency, and supporting sustainable agricultural practices in rural areas. The technology has strong potential for replication and integration into broader circular agriculture systems.